Optimal timing for early surgery in infective endocarditis: a meta-analysis(†) - Liang, Fuxiang (Interact Cardiovasc Thorac Surg, 2016)
To systematically review early surgery and the optimal timing of surgery in patients with infective endocarditis (IE), a search for foreign and domestic articles on cohort studies about the association between early surgery and infective endocarditis published from inception to January 2015 was conducted in the PubMed, EMBASE, Chinese Biomedical Literature (CBM), Wanfang and Chinese National Knowledge Infrastructure (CNKI) databases. The studies were screened according to the inclusion and exclusion criteria, the data were extracted and the quality of the method of the included studies was assessed. Then, the meta-analysis was performed using the Stata 12.0 software. Sixteen cohort studies, including 8141 participants were finally included. The results of the meta-analysis revealed that, compared with non-early surgery, early surgery in IE lowers the incidence of in-hospital mortality [odds ratio (OR) = 0.57, 95% confidence interval (CI) (0.42, 0.77); P = 0.000, I(2) = 73.1%] and long-term mortality [OR = 0.57, 95% CI (0.43, 0.77); P = 0.001, I(2) = 67.4%]. Further, performing operation within 2 weeks had a more favourable effect on long-term mortality [OR = 0.63, 95% CI (0.41, 0.97); P = 0.192, I(2) = 39.4%] than non-early surgery. In different kinds of IE, we found that early surgery for native valve endocarditis (NVE) had a lower in-hospital [OR = 0.46, 95% CI (0.31, 0.69); P = 0.001, I(2) = 73.0%] and long-term [OR = 0.57, 95% CI (0.40, 0.81); P = 0.001, I(2) = 68.9%] mortality than the non-early surgery group. However, for prosthetic valve endocarditis (PVE), in-hospital mortality did not differ significantly [OR = 0.83, 95% CI (0.65, 1.06); P = 0.413, I(2) = 0.0%] between early and non-early surgery. We concluded that early surgery was associated with lower in-hospital and long-term mortality compared with non-early surgical treatment for IE, especially in NVE. However, the optimal timing of surgery remains unclear. Additional larger prospective clinical trials will be required to clarify the optimal timing for surgical intervention and determine its efficacy in PVE.